PENGARUH TOTAL QUALITY MANAGEMENT (TQM), SISTEM PENGUKURAN KINERJA, SISTEM PENGHARGAAN (REWARD) DAN KETIDAKPASTIAN LLINGKUNGAN TERHADAP KINERJA MANAJERIAL - Fidra Rezka Feranza (Pascasarjana Universitas Sultan Ageng Tirtayas, 2023)
This study aims to test the Effect of Total Quality Management (TQM), Performance Measurement System, Reward System(reward), and Environmental Uncertainty on Managerial Performance in the Hospitality Industry of Serang city and Cilegon city. The samples used in this study were middle-level managers from star-rated hotels in Cilegon city and Serang city. Data were collected by distributing questionnaires with purposive sampling techniques to respondents. The respondents in this study were managers with a total of 36 respondents. Data analysis techniques use quantitative methods with the help of SPSS software. The results of this study showed that total quality management had no effect on managerial performance with a calculated t value > t table (1.738 > 2.03951), the performance measurement system had no effect on managerial performance with a calculated t value > t table (1.076 > 2.03951), the reward system had a significant effect in a positive direction with a calculated t value < t table (3.745 < 2.03951) with a significant 0.001 < 0.05. and environmental uncertainty had no effect on managerial performance with a calculated t value > t table (-0.246 < 2.03951).